Comparison of OBGYN postgraduate curricula and assessment methods between Canada and the Netherlands: an auto-ethnographic study - Paternotte, Emma; Dijksterhuis, Marja; Goverde, Angelique; Ezzat, Hanna; Scheele, Fedde (Frontiers in Medicine, 2024)
Introduction Although the Dutch and the Canadian postgraduate Obstetrics and Gynecology (OBGYN) medical educaEon systems are similar in their foundaEons (programmaEc assessment, competency based, involving CanMED roles and EPAs) and comparable in healthcare outcome, the program structure and assessment methods differ considerably. Materials and Methods We compared both countries’ postgraduate educaEonal blueprints and used an auto- ethnographic method to gain insight in the effects of training program structure and assessment methods on how trainees work. The research quesEons for this study are: What are the differences in program structure and assessment program in Obstetrics and Gynecology postgraduate medical educaEon in the Netherlands and Canada and how does this impact the advancement to higher competency for the postgraduate trainee? Results We found four main differences. The first two differences are the duraEon of training and the number of EPAs defined in the curricula. However, the most significant difference is the way EPAs are entrusted. In Canada supervision is given regardless of EPA competence, whereas in the Netherlands being competent means being entrusted, translaEng into meaningful and pracEcal independence in the workplace. Another difference was that Canadian OBGYN trainees have to pass a summaEve wriUen and oral exit exam. This difference in assessment program is largely explained by cultural and legal aspects of postgraduate training and consequent differences in licensing pracEce. Discussion Despite the fact that programmaEc assessment is the foundaEon for assessment in medical educaEon both in Canada and in the Netherlands, the significance of entrustment differs. Trainees are confused over the difference in formaEve and summaEve assessment. They experience both formaEve and summaEve forms of assessment as a judgement of their competence and progress. Based on this auto-ethnographic study, the possibility to further harmonizaEon of the OBGYN PGME in Canada and the Netherlands seems limited.